1995
DOI: 10.1159/000133900
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of five loci from human chromosome 8q onto sheep chromosome 9

Abstract: Using a chromosomally characterized minipanel of sheep × hamster cell hybrids, five new loci, including carbonic anhydrase II (CA2), calbindin 1 (28 kDa) (CALB1), corticotropin releasing hormone (CRH), cytochrome P450 11B subfamily XIB (steroid-11-β-hydroxylase), polypeptide 1 (CYP11B1), and interleukin 7 (IL7), have been assigned to sheep chromosome 9. A homolog of mosome 9 as the sheep equivalent of cattle chromosome 14 and indicates that CALB1, CYP11B1, and IL7, which have not been mapped on the cattle geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Isotopic in situ hybridization was performed essentially as described by BROAD et al (1995) on early metaphase chromosomes from a ram with three Robertsonian translocations, karyotype 48XY, t,t,t,t,t,t,, where t, = rob 6;24, t, = rob 9;10, and t, = rob 7;25. The chromosomes were Q-banded before hybridization and identified according to the Reading standard karyotype (FORD et al 1980;ANSARI et al ,1994.…”
Section: Methodsmentioning
confidence: 99%
“…Isotopic in situ hybridization was performed essentially as described by BROAD et al (1995) on early metaphase chromosomes from a ram with three Robertsonian translocations, karyotype 48XY, t,t,t,t,t,t,, where t, = rob 6;24, t, = rob 9;10, and t, = rob 7;25. The chromosomes were Q-banded before hybridization and identified according to the Reading standard karyotype (FORD et al 1980;ANSARI et al ,1994.…”
Section: Methodsmentioning
confidence: 99%
“…The IL7 gene has been also mapped to bovine chromosome 14 (BTA 14) (Barendse et al, 1997;Band et al, 2000) and ovine chromosome 9 (OVR 9) (Broad et al, 1995). It has been already shown that BTA 14 and OVR 9 have chromosome-wide synteny with the long arm of human chromosome 8 (Band et al, 2000;Burkin et al, 1997).…”
Section: Chromosome Location Of Porcine Il7genementioning
confidence: 99%
“…Isotopic in situ hybridization was performed as previously described (Broad et al 1995b) on early metaphase chromosomes from a ewe with three Robertsonian translocations (karyotype 49XX, t,t,t2t,t,, where t, =rob 6;24, t, = rob 9;10, and t,=rob 7;25). The chromosomes were Qbanded before hybridization and identified as in Ansari et al (1993a) according to the Reading standard karyotype (Ford et al 1980).…”
Section: Hybridization Reactionsmentioning
confidence: 99%